THE DEVELOPMENT OF CLASH OF CHAMPIONS GAME-BASED TEACHING MATERIALS TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS IN ISLAMIC RELIGIOUS EDUCATION - Ichwanudin, Moch.; Siti Nurjanah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study aims to develop student worksheet (LKPD) teaching materials based on the Clash of Champions educational game to enhance the critical thinking skills of eighth-grade students in Islamic Religious Education (PAI). The research employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation phases. Validation instruments involved media and content experts, along with practicality questionnaires for teachers and students. The results showed media validity at 98% and content validity at 92%. Practicality scores reached 96% (teachers) and 97% (students). The effectiveness test revealed an increase in students’ average scores from 63% to 98%, with an N-Gain score of 0.94 (high category). These findings indicate that the game-based LKPD is effective in fostering critical thinking in Islamic Education learning. Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa Lembar Kerja Peserta Didik (LKPD) berbasis game edukatif Clash of Champions guna meningkatkan kemampuan berpikir kritis siswa kelas VIII pada mata pelajaran Pendidikan Agama Islam (PAI). Penelitian menggunakan model pengembangan ADDIE yang mencakup analisis, desain, pengembangan, implementasi, dan evaluasi. Instrumen validasi melibatkan ahli media dan materi, serta angket kepraktisan guru dan siswa. Hasil validasi menunjukkan tingkat kevalidan 98% (media) dan 92% (materi). Kepraktisan memperoleh skor 96% (guru) dan 97% (siswa). Efektivitas bahan ajar ditunjukkan melalui peningkatan nilai rata-rata dari 63% menjadi 98% dengan N-Gain sebesar 0,94, tergolong kategori tinggi. Temuan ini menunjukkan bahwa bahan ajar LKPD berbasis game efektif meningkatkan kemampuan berpikir kritis dalam pembelajaran PAI.